2021
DOI: 10.1111/bjet.13116
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of technology‐supported personalised learning in low‐ and middle‐income countries: A meta‐analysis

Abstract: Digital technology offers the potential to address educational challenges in resource‐poor settings. This meta‐analysis examines the impact of students' use of technology that personalises and adapts to learning level in low‐ and middle‐income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 68 publications
2
42
1
6
Order By: Relevance
“…Several meta-analyses highlighted the positive effect of feedback on student performance (Hattie & Timperley, 2007;Wisniewski et al, 2020) and a long research tradition focuses adaptive teaching concepts, in which teachers adjust their teaching approach to individual students learning (Brühwiler & Blatchford, 2011;Hardy et al, 2011;Hattie, 2009). In recent decades, this personalized learning has been closely linked to digital media in educational research, and has been found to have positive impacts on learning outcomes (Major et al, 2021;Zheng et al, 2022). The data from the present study did not show an overall positive effect of personalized teaching.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Several meta-analyses highlighted the positive effect of feedback on student performance (Hattie & Timperley, 2007;Wisniewski et al, 2020) and a long research tradition focuses adaptive teaching concepts, in which teachers adjust their teaching approach to individual students learning (Brühwiler & Blatchford, 2011;Hardy et al, 2011;Hattie, 2009). In recent decades, this personalized learning has been closely linked to digital media in educational research, and has been found to have positive impacts on learning outcomes (Major et al, 2021;Zheng et al, 2022). The data from the present study did not show an overall positive effect of personalized teaching.…”
Section: Discussioncontrasting
confidence: 59%
“…While some children were able to learn with learning management systems (LMS), videoconferencing or interactive webinars other children did only receive worksheets without any feedback by their teachers (Porsch & Porsch, 2020). In general, recent findings suggest that technology-enhanced personalized learning is associated with better learning outcomes, higher motivation to learn, and more positive student perceptions of learning (Major et al, 2021;Zheng et al, 2022). Accordingly, the positive effects for personalized learning (Zhang et al, 2020) and feedback (Wisniewski et al, 2020) that have been known for decades in traditional classrooms settings can also be observed for digital learning environments.…”
Section: Basic Mathematical Skills and Distance Learning In Germanymentioning
confidence: 99%
“…Güler, 2018), internet ders öncesi hazırlık, ders içi çalışmalar ya da araştırmalar, interaktif alıştırmalar yapma gibi etkinliklerde kullanılmaktadır (Sağıroğlu, Bülbül, Kılıç & Küçükali, 2020). Bilişim teknolojilerindeki hızlı gelişmeler günlük hayatı etkilediği gibi eğitim ortamlarını değiştirdiğinden (Altıok, Yükseltürk & Üçgül, 2017), eğitim araştırmacılarının eğitim ortamlarında dijital teknolojilerin kullanımı konusuna giderek daha fazla odaklandıkları görülmektedir (Major, Francis & Tsapali, 2021). Alanyazın incelendiğinde bazı araştırmacıların (Chu, Hwang & Tseng, 2010) öğrencilerin bilişsel davranışsal ve duygusal yetkinliklerini geliştirebileceği düşüncesinden hareketle eğitim ortamlarında farklı dijital teknolojilerin kullanılmasının önemli olduğuna dikkat çektikleri anlaşılmaktadır.…”
Section: Suggestionsunclassified
“…Gambar 12. Rekapitulasi Tiap Aspek Media Pembelajaran Padlet Keberadaan pandemi Covid 19 telah mengubah kebiasaan belajar, kebiasaan belajar dari rumah membuat guru berperan lebih kreatif dalam membuat desain pembelajaran, bahan ajar berbasis elektronik untuk mendukung pembelajaran jarak jauh [19]- [22]. Kebanyakan siswa kini tidak bisa lepas dari perangkat gawai pintar dengan platform Android dan Mac OS [23].…”
Section: Gambar 2 Petunjuk Pada Padletunclassified